Arteriovenous uterine malformation developed from an interstitial pregnancy on residual tubal stump: A critical managment in a fertile woman. Issue 1 (14th October 2019) - Parisi, Silvia; Garofalo, Anna; Alemanno, Maria Grazia; Chiado Fiorio Tin, Michela; Petruzzelli, Paolo; Viora, Elsa
Abstract: Uterine arteriovenous malformations are rare conditions with diverse clinical presentation that range from asymptomatic patients to different degrees of menorrhagia, commonly associated with previous pregnancy or uterine trauma. This case report describes a 36‐year‐old woman who presented with ultrasound diagnosis of interstitial pregnancy on residual right tube stump 4 months after a laparoscopic salpingectomy for extrauterine pregnancy. She started treatment with methotrexate; afterwards serum human chorionic gonadotropin levels and ultrasound follow‐ups were scheduled. While serum human chorionic gonadotropin levels were progressively reducing, transvaginal ultrasound follow‐ups showed a persistent anechoic mass on right rube stump, with increased peripheral high flow vascularity: highly suspicious for a uterine arteriovenous malformation. A laparoscopy was performed with a tumorectomy of the mass. The histopathological exam of the specimen confirmed uterine arteriovenous malformation. Patient successfully became pregnant 2 years later, with an eventless pregnancy and a vaginal delivery without complications.